Implementation of the Science Learning Model on Critical Thinking Abilities of Middle School Students: A Review - Hanafi, Muhammad; Doyan, Aris (International Journal of Science Education and Science, 2024)
Critical thinking skills are one of the skills that students really need. This analysis is an analysis that aims to determine effective learning models to improve students' critical thinking skills in science learning. The search results obtained were 25 articles that were relevant for analysis. The results of the analysis show that one effective learning model is used to improve critical thinking skills, namely the discovery learning model with a score of 92.56.